Application of Stearic Acid for Solar Thermal Energy Storage in a Double Compartment Solar Box Cooker - Maina, M. B.; Shodiya, S.; Abdulrahim, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Energy storage in some form is the need of the hour to even out the mismatch between energy supply and demand. Thermal Energy Storage (TES) system employing a phase change material (PCM) has been widely considered as an effective way to store and retrieve energy due to its high heat storage capacity at almost constant temperature during the phase change. In this work, an energy storage system was designed to study the heat transfer characteristics of stearic acid (as a phase change material in a double compartment solar box cooker (DCSBC) fabricated using wooden materials with high thermal energy storage system. In order to analyze the various characteristics of the PCM, the Bureau of Indian Standards (BIS) was used throughout the experiment. Investigations were performed to determine the first and second figure of merits (F1 and F2) of compartments 1 and 2 (C1 and C2) simultaneously. The results for F1 were found to be (C1= 0.14 and C2= 0.15) and F2 were (C1=0.47 and C2= 0.4) while the overall thermal efficiency of the cooker after water boiling test for C1 with 2.5kg and C2 with 3kg of water were deduced to be 77% for C1 and 92% for C2 after six hours of the load test, showing considerable temperature increase and extension of heat retention making possible to cook the dinner and even breakfast the next day.